Double-networks based on pH-responsive, amphiphilic "core-first" star first polymer conetworks prepared by sequential RAFT polymerization. Issue 1 (30th September 2016) - Kitiri, Elina N.; Patrickios, Costas S.; Voutouri, Chrysovalantis; Stylianopoulos, Triantafyllos; Hoffmann, Ingo; Schweins, Ralf; Gradzielski, Michael
Abstract : Double-networks based on amphiphilic polymer conetworks synthesized using RAFT polymerization were prepared, exhibiting pH-responsiveness, nanophase separation and enhanced mechanical properties. Abstract : This manuscript presents the preparation and study of a new double-network hydrogel system, comprising an amphiphilic, pH-responsive first polymer conetwork synthesized via reversible addition–fragmentation chain transfer (RAFT) polymerization, and a second hydrophilic polymer network prepared via free radical photopolymerization. The amphiphilic character of the first conetwork led to its phase separation on the nanoscale, as indicated by small-angle neutron scattering (SANS) in deuterium oxide, whereas the presence of segments consisting of tertiary amine-bearing monomer repeating units resulted in pH-dependent equilibrium swelling in water. Finally, the introduction of a second, reinforcing network into the structure of the first conetwork produced a double-network hydrogel system with mechanical properties (compressive stress and strain at break, and low-strain elastic modulus) superior to those of the first conetwork. Thus, the present complex hydrogel system bears three important functions: high mechanical properties to endure an environment with high stresses, hydrophobic pockets to solubilize non-polar substances within an overall aqueous milieu, and an ability to respond to changes in pH. Such multi-functional water-swollen polymer systems can pave the way toward next-generation biomaterials.